Effect of plant litter burial on soil dissolved organic matter in the Yellow River Delta wetland, China - Linping Xie; Yutong Yan; Min Wang; Guangang Hu; Xia Sun; Jianbu Wang; Ming Xin; Qinsheng Wei; Baodong Wang (Marine Environmental Research, 2026)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

Synergy between Mo dopants and Ni vacancies in NiOOH for enhanced oxygen evolution reaction - Xiaoyi Dou; Ding Yuan; Xiaopeng Liang; Kepeng Song; Riming Hu; Lei Zhang; Jagadish Chandra Roy; Xuchuan Jiang; Hua Kun Liu; Yuhai Dou; Linping Yu (Chemical Engineering Journal, 2023)

Identification of a novel frameshift mutation in the SCNN1B causing Liddle syndrome - Yi Qu; Yiting Lu; Di Zhang; Xinchang Liu; Peng Fan; Jiexin Chen; Hanbo Zhang; Kunqi Yang; Tao Tian; Yi Zhou; Qiongyu Zhang; Yu Zhang; et al. (Science Bulletin, 2023)

New insights into Human Hematopoietic Stem and Progenitor Cells via Single-Cell Omics - Yawen Zhang; Yaojin Huang; Linping Hu; Tao Cheng (Stem Cell Reviews and Reports, 2022)
Residing at the apex of the hematopoietic hierarchy, hematopoietic stem and progenitor cells (HSPCs) give rise to all mature blood cells. In the last decade, significant progress has been made in single-cell RNA sequencing as well as multi-omics technologies that have facilitated elucidation of the heterogeneity of previously defined human HSPCs. From the embryonic stage through the adult stage to aging, single-cell studies have enabled us to trace the origins of hematopoietic stem cells (HSCs), demonstrating different hematopoietic differentiation during development, as well as identifying novel cell populations. In both hematological benign diseases and malignancies, single-cell omics technologies have begun to reveal tissue heterogeneity and have permitted mapping of microenvironmental ecosystems and tracking of cell subclones, thereby greatly broadening our understanding of disease development. Furthermore, advances have also been made in elucidating the molecular mechanisms for relapse and identifying therapeutic targets of hematological disorders and other non-hematological diseases. Extensive exploration of hematopoiesis at the single-cell level may thus have great potential for broad clinical applications of HSPCs, as well as disease prognosis. Graphical abstract